Pension adjustment showdown: tripartite between Aminah Ahmad vs Pensions Adjustment (Amendment) Act 2013: The Parental Act v Art. 147 of the Federal Constitution - Shariffuddin, Norashikin; Ahmad Mustafa, Mimi Sofiah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In Malaysia, civil servant pensions were once tied to current salary increases, ensuring financial stability for retirees. However, the 2013 amendment replaced this system with a fixed 2% annual increase, sparking concerns among retirees like Aminah Ahmad about fairness and declining income over time.